Desenvolvimento biológico de marava arachidis yersin, 1860 - Nascimento, Mariana Lima do (2018)
Sugarcane (Saccharum spp.) Is currently one of the main crops of Brazilian agriculture. However, some factors are still limiting in the optimization of its production. During its development sugarcane faces a series of phytosanitary problems, among them caused by insects, Diatraea saccharalis (Diatraea ssp.) Popularly known as a sugarcane borer considered one of the main species responsible for causing insults to this culture, causing great economic damages. In order to eliminate the impact caused by the application of chemical insecticides, new management strategies that use alternative methods such as biological control have been proposed and evaluated. The insects belonging to the order Dermaptera, are characterized as organisms with good predatory capacity. Among the biological agents with characteristics suitable for this purpose, dermápteros have aroused great attention, as they are entomophagous predators with high attack capacity and feed on several prey, particularly eggs and immature stages of insects of various orders. The objective of this research was to evaluate the biological and morphometric aspects of Marava arachidis in artificial diet and the predation capacity of the scallop when fed with D. saccharalis. The research was conducted at the Laboratory of Invertebrate Zoology, belonging to the Department of Biological Sciences of the Center of Agricultural Sciences of the UFPB-PB, the average temperature of 25 ± 1ºC and photophase of 12 hours. The cultivations of M. arachidis and D. saccharalis were maintained. For each instar of the scissors were selected 10 individuals from the breeding kept in the laboratory, being fed with artificial diet, eggs and caterpillars from the 1st to the 6th instar of D. saccharalis. To evaluate the adult stage, 10 males and 10 females were selected, forming 10 couples. Nitrile number, number of nymphs, total body size, capsule size, weight, mortality, as well as the mean and total consumption of eggs and caterpillars of D. saccharalis were reported. It was observed that even in relation to different food sources, the predator presented four instars for the nymphal phase and the adult phase; all instars of M. arachidis predate the different phases of D. saccharalis, proving to be an efficient control agent of this pest, since it consumed a large number of both eggs and caterpillars, for this reason this species presents possibility of use in biological control programs.